2019
DOI: 10.1002/jbt.22438
|View full text |Cite
|
Sign up to set email alerts
|

Hematological effects of ultrafine carbon black on red blood cells and hemoglobin

Abstract: The harmful effects of ultrafine particles (UFPs) in the atmosphere have caused widespread concern. Ultrafine carbon black (UFCB) is an important component of UFPs. In this study, we explored the impact of UFCB on the structure, the antioxidant defense system, and the ATPase activity of human red blood cells (hRBCs). It was found that UFCB decreased the activity of SOD (73.58%), CAT (89.79%), and GSH‐Px (81.02%), leading to oxidative stress in hRBCs. UFCB had no destructive effect on the structure of hRBCs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…The lowest concentration, on the other hand, does not reach 50% hemolysis at all. In accordance with our results, previous studies have reported that carbonaceous ultrafine particles have minimal hemolytic effects, indicating limited damage to the erythrocyte membrane [60].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The lowest concentration, on the other hand, does not reach 50% hemolysis at all. In accordance with our results, previous studies have reported that carbonaceous ultrafine particles have minimal hemolytic effects, indicating limited damage to the erythrocyte membrane [60].…”
Section: Discussionsupporting
confidence: 93%
“…Erythrocyte osmotic fragility test: The methodology utilized for the present study includes an accurate control for the possible presence of blood diseases that might generate false positive or false negative results. Hemolysis caused by different types of nanoparticles (polystyrene, titania, magnetite, gold, silver, silica, zincite, and selenium) has been widely reported in the literature [ 33 , 37 , 59 , 60 , 61 ]. The osmotic fragility (OF) test is commonly used to evaluate the erythrocyte membrane and diagnose hemolytic anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UFCB is usually a kind of nanomaterial which is difficult to dissolve in water. Pan et al 20 use hydrogen peroxide to modify UFCB to enhance the water solubility of UFCB. Qu et al 21 use ozone to modify UFCB.…”
Section: Modification Of Carbon Blackmentioning
confidence: 99%